Cross-regional variations of Covid-19 mortality in Italy: an ecological study. (18th January 2021) - Oliva, Cristina; Di Maddaloni, Francesco; Marcellusi, Andrea; Favato, Giampiero
ABSTRACT: Background: Disparities in cross-regional coronavirus disease 2019 (Covid-19) mortality remain poorly understood. The association between pre-epidemic health and epidemic mortality can inform a policy response to future outbreaks. Method: We conducted an ecological study of the association between the cumulative deaths attributed to Covid-19 epidemic in the 20 Italian regions and nine determinants of population health derived from a systematic review of the literature. We used a multiple least square regression to predict the cross-regional variation in mortality observed from the onset of the epidemic to 23 September 2020. Results: Four independent variables best explained the cross-regional differences in the number of deaths attributed to Covid-19: the force of infection, population density, number of elderly living in assisted facilities and the standard rate of diabetes. The semi-partial correlation coefficients suggest that the force of infection and the number of elderly residents in nursing homes were the dominant predictors of the number of deaths attributed to Covid-19. Statistical controls and validation confirmed the generalizability of the predictive model. Conclusions: Our findings indicate that a significant reduction of social contacts in main metropolitan areas and the timely isolation of elderly and diabetic residents could significantly reduce the death toll of the next wave of Covid-19 infection in Italy.